2021
DOI: 10.25115/eea.v39i5.5065
|View full text |Cite
|
Sign up to set email alerts
|

Distance Learning Technologies and Innovations in Education for Sustainable Development

Abstract: The article analyzes technologies for teachers’ professional development to work online in education for sustainable development. The authors emphasize that education for sustainable development (ESD) promotes developing the knowledge, skills, understanding, values and actions required to create a sustainable world, which ensures environmental protection and conservation, promotes social equity and encourages economic sustainability. ESD must engage a wide range of stakeholders from government, private sector,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In general, researchers agree that the digital approach in pedagogy and psychology of the future has the potential to change the way we learn and support personal development. Trends in the use of digital technologies in education and psychology promise more individualised and accessible services but require attention to globalisation challenges and cybersecurity issues (Semenets-Orlova et al, 2021b;Mahanta, 2022). Understanding and addressing these challenges is an important task for researchers, practitioners, and a solution to ensure quality education and psychological support in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, researchers agree that the digital approach in pedagogy and psychology of the future has the potential to change the way we learn and support personal development. Trends in the use of digital technologies in education and psychology promise more individualised and accessible services but require attention to globalisation challenges and cybersecurity issues (Semenets-Orlova et al, 2021b;Mahanta, 2022). Understanding and addressing these challenges is an important task for researchers, practitioners, and a solution to ensure quality education and psychological support in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Ali (2022) identified the effectiveness of immersive technologies in the education sector of the future. At the same time, Semenets-Orlova et al (2021b) identified the main innovations in the distance education system. Humeniuk and Romaniuk (2023) describe the peculiarities of the development of information and communication technologies in the field of education through the prism of the futuristic aspect.…”
mentioning
confidence: 99%
“…This problem was encountered by many out-of-school learning curricula: even when they offered a digital fallback for processing at home, it was questionable what advantages would accrue from this facility. In addition to the complexity of ESE content, teachers also faced the methodological and technical challenges of emergency distance teaching [26]. Other studies indicate that low-achievers and marginalized groups had more problems with distance learning than high-achievers [27,28].…”
Section: Impact Of Distance Education On Ese Learning Outcomementioning
confidence: 99%
“…The educational technology is a theory and practice in the design, development, utilization, management, and evaluation of processes and resources for learning [1]. Educational Technology is an effort to facilitate the formation and development of individual competencies which serve as prerequisites for developing life skills at the family, community, and industry levels [2]. Learning tools based on e-learning can be developed based on models integrated with approaches to support students' abilities.…”
Section: Introductionmentioning
confidence: 99%